Aspects concerning Șugău Cave topoclimate. - M. CIGHER (Riscuri şi Catastrofe, 2017)

(untitled)
The work presents a preliminary report on the diurnal topoclimatic characteristics specific to Şugău Cave, located in the southwest part of Giurgeu Mountains (Suseni, Harghita, Romania), in terms of the main topoclimatic parameters - temperature and relative humidity. The frequency of data for this study is hourly and covers the period May 15 - June 24, 2017, with high tourist flows. The main topoclimatic alignment represented by the Gemini Datalogger sensors follows the touristic gallery from the Entrance (Intrare) to the Music Hall (Sala Muzicii). In opposition, the sensors in the Great Hall (Sala Mare) and the Wonderful Hall (Sala Minunată) are meant to capture the topoclimatic features unaltered by mass tourism. Following the preliminary observation it is noted that the diminution of the diurnal thermal amplitudes occurs, on the tourist section, between 60-80 m away from the entrance, in G04 and G05 points, the average diurnal thermal amplitude is 0.2ºC. The average daily temperature on this alignment reaches the minimum value in the Music Hall (7.26 ºC), a value with 0.26ºC higher than that measured in the Grand Hall and 0.25ºC higher than that recorded in the Wonderful Room – Chandelier (Sala Minunată - Candelabru). The influences of the underground watercourse are strongly felt in the Active Gallery (Galeria Activă) with regard to temperature, stations G07 and G08 recording average daily temperatures of 5.71°C and 5.92°C respectively. The great topoclimatic stability in this gallery is also underlined by the extremely low diurnal average amplitude: 0.03ºC in station G07 and 0.06ºC in station G08. Stability meroclimate in this case is reached less than 10 m away from the entrance. Regarding relative humidity, except for the surface reporting station of the G02 and G03 sensors, all other sensors do not exhibit oscillations of the values. Starting with G03, the relative humidity values are over 97.5%.